Absence of peripheral pulses and risk of major vascular outcomes in patients with type 2 diabetes - Mohammedi, K; Woodward, M; Zoungas, S; Q, L; Harrap, Stephen, S; Patel, A; Marre, M; Chalmers, J (American Diabetes Association, 2016)
Background: The burden of vascular diseases remains substantial in patients with type 2 diabetes, requiring identification of further risk markers. We tested the absence of dorsalis pedis and posterior tibial pulses as predictors of major macrovascular and microvascular events, death, and cognitive decline in this population. Methods: Data were derived from 11120 patients with type 2 diabetes in the Action in Diabetes and Vascular Disease: PreterAx and DiamicroN Modified-Release Controlled Evaluation (ADVANCE) study. Absent peripheral pulses at baseline were defined as absence of at least one dorsalis pedis or posterior tibial pulse. Results: Absent, compared to present, peripheral pulses (n=2218) were associated with increased 5-year risks for major macrovascular events (HR 1.47, 95%CI 1.28-1.69, p<0.0001), myocardial infarction (1.45 [1.13-1.87], p=0.003), stroke (1.57 [1.23-2.00], p=0.0003), cardiovascular death (1.61 [1.33-1.95], p<0.0001), heart failure (1.49 [1.21-1.84], p=0.0002), all-cause mortality (1.48 [1.29-1.71], p<0.0001), major microvascular events (1.17 [1.00-1.36], p=0.04), nephropathy (1.24 [1.00-1.54], p=0.04), end stage renal disease or renal death (2.04 [1.12-3.70], p=0.02), and peripheral neuropathy (1.13 [1.05-1.21], p=0.0008) after multiple adjustment. Participants with absent dorsalis pedis or posterior tibial pulses displayed comparable HRs. Risks increased proportionally with the number of absent peripheral pulses, with the highest risks observed in patients with 3 or 4 absent pulses. Every additional absent pulse increases risk of all outcomes. Conclusions: Absent dorsalis pedis and/or posterior tibial pulses are independent predictors of major vascular outcomes in patients with type 2 diabetes. These simple clinical indicators should be used to improve risk stratification and treatment of these patients.